Объяснение:
Дано:
t1 = 32 c
t2 = 64 c
x = 33 см
L1 - ?
L2 - ?
T = t/N
N1 = N1 = N = const
T1 = t1/N ; T2 = t2/N
T = 2π√( L/g )
T² = ( 4π²L )/g
L = ( T²g )/( 4π² )
L1 = ( T1²g )/( 4π² ) ; L2 = ( T2²g )/( 4π² )
Пусть
L1 = a
L2 = a + x
L1/L2 = ( ( T1²g )/( 4π² ) )/( ( T2²g )/( 4π² ) )
L1/L2 = T1²/T2²
L1/L2 = ( t1/N )²/( t2/N )²
L1/L2 = t1²/t2²
a/( a + x ) = t1²/t2²
a/( a + 33 ) = 32²/64²
a/( a + 33 ) = 0,25
a = 0,25( a + 33 )
a = 0,25a + 8,25
a - 0,25a = 8,25
a( 1 - 0,25 ) = 8,25
0,75a = 8,25
a = L1 = 11 см
Тогда
L2 = 11 + 33 = 44 см